A case report of acquired methemoglobinemia rescued by veno-venous extracorporeal membrane oxygenation. Issue 15 (16th April 2021) - Lien, Yu-Hsuan; Lin, You-Cian; Chen, Robert Jeenchen
Abstract: Rationale: Severe methemoglobinemia (Met-Hb) is rare. The delayed diagnosis and treatment often cause further damage. The management of cellular hypoxemia is challenging and the use of extra-corporeal membrane oxygenation (ECMO) has never been reported. Patient concerns: The young patient, healthy with unremarkable past medical history, was sent to emergency room with out-of-hospital circulatory arrest (OHCA) and severe generalized cyanosis. His family reported he ingested sodium nitrite accidentally. Diagnoses: After successful resuscitation and return of spontaneous circulation (ROSC), the paradoxically normal arterial blood gas (ABG) with the unusual brownish blood led to the suspicion of Met-Hb. The lab test confirmed it and showed a very high level of 80%. Interventions: Because of recovered and normal cardiac function, we placed veno-venous extracorporeal membrane oxygenation (VV-ECMO) for tissue hypoxemia in addition to exchange transfusion, vitamin C, and methylene blue. Outcomes: Met-Hb blood level dropped rapidly. After vigorous rehabilitation for weeks, the patient was able to be discharged home without major neurological sequela. Lessons: VV-ECMO can hyper-oxygenate the hypoxemic tissue regardless the etiology and minimize hypoxemia-reperfusion injury while awaiting the definite diagnosis and therapy.